Medical relief for the 2011 Japan earthquake: A nursing account1. (4th December 2013) - Mitani, Satoko; Kako, Mayumi; Mayner, Lidia
Abstract In 2011 the east coast of Japan experienced a massive earthquake which triggered a devastating tsunami destroying many towns and killing over 15 000 people. The work presented in this paper is a personal account that outlines the relief efforts of the Humanitarian Medical Assistance team and describes the efforts to provide medical assistance to evacuees. The towns most affected had a large proportion of older people who were more likely to have chronic conditions and required medication to sustain their health. Since personal property was destroyed in the tsunami many older people were left without medication and also did not remember which type of medication they were taking. Some evacuees had brought a list of their medication with them, this assisted relief teams in obtaining the required medication for these people. The more successful evacuation centers had small numbers of evacuees who were given tasks to administer the center that kept them occupied and active.